2008
DOI: 10.1016/j.tips.2008.07.009
|View full text |Cite
|
Sign up to set email alerts
|

An escort for GPCRs: implications for regulation of receptor density at the cell surface

Abstract: G-protein-coupled receptors (GPCRs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
86
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 82 publications
0
86
0
2
Order By: Relevance
“…2D), which also indicated the D1R-YFP internalization caused by drug treatments. 3.3 D5R did not translocate to cell surface from intracellular compartments after the treatment It has been reported that the GPCRs can not only be internalized from the cell surface but also display the regulated translocation to the cell surface from intracellular compartments [11] . As D5R locates both in the plasma membrane and in the intracellular compartments in resting conditions, there raises the question: whether D5R would be translocated by the drug treatment?…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…2D), which also indicated the D1R-YFP internalization caused by drug treatments. 3.3 D5R did not translocate to cell surface from intracellular compartments after the treatment It has been reported that the GPCRs can not only be internalized from the cell surface but also display the regulated translocation to the cell surface from intracellular compartments [11] . As D5R locates both in the plasma membrane and in the intracellular compartments in resting conditions, there raises the question: whether D5R would be translocated by the drug treatment?…”
mentioning
confidence: 91%
“…The trafficking of GPCRs between cell surface and intracellular compartment indicates an important functional regulation [11] . Two situations are included in the trafficking process: one is the internalization of the receptor from the cell surface to the intracellular compartment; the other is the translocation to cell surface from the intracellular compartment.…”
Section: Introductionmentioning
confidence: 99%
“…Most GPCRs are found as stocks of functional receptors retained mainly in the ER or Golgi apparatus. These GPCRs are mobilized to the cell surface by their interactions with escort proteins (26,27). For instance, the receptor activity-modifying protein 2 (RAMP2) increases CRF 1 R (28) and RAMP1 increases calcitonin-receptor-like receptor (CRLR) (29) in the plasma membrane.…”
mentioning
confidence: 99%
“…Cependant, de nombreuses observations indiquent que le trafic de ces récepteurs vers la surface cellulaire pourrait être régulé par des interactions avec certaines protéines et par des signaux extra-cellulaires. Des études récentes démontrent que pour de nombreux RCPG, une proportion importante des récepteurs est retenue dans des compartiments intracellulaires comme le réticulum endoplasmique (RE) ou l'appareil de Golgi [1]. Ces « réserves » peuvent être mobilisables vers la membrane plasmique en réponse à une stimulation physiologique qui nécessite une augmentation rapide de la réceptivité cellulaire [2,3].…”
unclassified
“…De plus, dans des expériences d'expression des RCPG dans des cellules modèles ne les exprimant pas naturellement (expression hétérologue), il a été montré que beaucoup d'entre eux nécessitent une association à des protéines d'escorte ou à des chaperons moléculaires pour être correctement exprimés à la surface. Les récepteurs olfactifs en sont un des exemples les plus connus et cette caractéristique a pendant longtemps empêché leur étude fonctionnelle in vitro [1]. Dans plusieurs pathologies humaines, comme le diabète insipide néphrogénique, la rétinite pigmentaire, l'obésité ou l'hypogonadisme, des mutations somatiques des RCPG [4] ou de protéines nécessaires à leur maturation [5], sont à l'origine d'un excès de rétention dans les compartiments intracellulaires.…”
unclassified